Combination of α-lactalbumin and gum arabic for microencapsulation of L-menthol: The effects on flavor release during storage and rehydration. (May 2023) - Peng, Siyi; Zhao, Jiajia; Wang, Yaru; Chen, Fang; Hu, Xiaosong; Ma, Lingjun; Ji, Junfu
Graphical abstract: Highlights: L-menthol-based products generally show the flavor loss and the inadequate release. SFD process produced the spherical microparticles with highest porosity of 86.82 %. SFD microparticles enhanced the flavor retention during the high humidity storage. The porous structures caused the rapid rehydration and flavor release in liquids. The release behaviors of L-menthol in SFD powders followed the Fickian diffusion. Abstract: L-menthol-containing food products generally show the flavor loss during storage due to their high volatility. The hydrophobicity of L-menthol also causes the inadequate flavor release during rehydration. In this study, the stability of L-menthol was enhanced by microencapsulation and the effect of different powder drying techniques was also investigated. The highest efficiency (76.58–78.66 %) and loading content (18.58–28.35 mg/g) of encapsulations were obtained by using a mass ratio of 2:1(α-LA: GA). Then they were dried by non-thermal spray freeze drying (SFD) technique compared to spray drying (SD) and freeze-drying (FD) process. The SFD particles were shown to be spherical and porous with the highest porosity (86.82 %). α-LA/GA based microparticles with spherical shapes were demonstrated to largely enhance flavor retention during high humidity storage. In addition, the porous structures of SFD powders could cause rapid rehydration in liquid models, and the release behaviors of loaded L-menthol followed the Fickian diffusion. Consequently, the SFD technique shows great potential to produce microparticles by regulating the release behaviors of L-menthol during storage and rehydration.